On the Conditions for the Introducing Distance Learning in Russian Universities - A. V. Borovskikh (Moscow Polytechnic University, 2023)
Modern computer and Internet technologies make it possible not only to transfer educational materials to digital media, but also to implement in a remote format various teaching methods,  diagnostics,  individualization  of  educational  interests  and  trajectories,  and  much  more. In addition, modern technologies in this area allow us to do what was simply impossible within the framework of the conventional education system. But the issue of a reasonable measure of the use of these technologies and the adequate setting and implementation of tasks in this direction requires special work. The article presents the results of this kind of work carried out on the basis of a program-project approach. Although the work was carried out within the framework of the assignment of  the  FEMU  to  classical  universities  for  mathematical  education,  the  specifics  of  universities  and mathematical education were not significant. The assignment was to determine the readiness of the mathematical faculties of universities for the systematic use of distance learning through an expert survey  of  FEMU  members.  The  relevance  of  the  question  of  the  timeliness  of  the  introducing  distance learning in a particular situation, on the one hand, and the problematic nature of this issue, due to the lack of proper systemic, logical grounds for its solution, prompted the author to apply his own method, which is conceptually different from the numerous surveys and "experiences" available in literature. The application of this method ("double inversion of position" or, in other words, "double negation": intent   - objections  - withdrawal of objections), made it possible to formulate three principal lists. The first contains an explicitly formulated framework in which the introducing distance learning makes sense; the second and third represent the research and development program necessary for the implementation of distance learning. And already on the basis of the first list, related to the current situation, a survey of experts was conducted, which made it possible to formulate the main conclusions on the problem under discussion. The results obtained fix a logical necessity that does not depend on private opinions or specific features of the situation.